9. The Effectiviteness of Jatropha salve (Jatropha curcas L) in Inflammatory Phase of cutaneous wound healing in Mice (Mus musculus) Histopathologically - Indra Sitorus; M Nur Salim; Nazaruddin Nazaruddin; Dwinna Aliza; Denny Irmawati; Awaluddin Awaluddin; Cut Nila Thasmi; Muslim Akmal; Dian Masyitha (Jurnal Medika Veterinaria, 2020)
This study aims to determine the effectiveness of 10% Jatropha salve (Jatropha curcas L. )    to inflammation reaction cutaneous wound healing in mice (Mus musculus ) in the inflammatory phase. This experiment used 9 male mices, weighing 25-40 grams and age 2-3 months old, were divided into three treatment groups, each treatment consisting of three mices. The wound were made along 2 cms in the back area. Wound therapy was carried out  twice a day for 3 days.  Group KI was administered  and given by yellow vaseline, KII was given 10% Jatropha salve, and KIII was given gentamicin salve. The parameters measured are the increase in the number infiltrations of inflammatory cells,  neovascular, and re-epitelization. All quantitative data were measured using ANOVA and continued with Duncan Test, the qualitative data were presented descriptively by showing the results of observation under a microscope. The statistical test on the infiltrations of inflammatory cells and neovasculars parameter 10% Jatropha salve group significantly different (P0.05) compared to KI and KIII group. Histopatologycal observations indicated the 10% Jatropha salve could be reduce the infiltrations of inflammatory cells, increase neovasculars and re-epitelization percentage. According to the result can be concluded the 10% Jatropha salve can accelerate the inflammation phase cutaneous wound healing in mice.